The Role of the Lingga Regency Government in Electricity Distribution in North Lingga Sub-district (Case Study in Pasir Lulun Preparatory Village) - Wahyudi, Haris; Kustiawan, Kustiawan; Putra, Ardi (Formosa Journal of Applied Sciences, 2024)
Rural areas are areas in Indonesia that are inhabited by a large proportion of the population. The population area is usually engaged in the agricultural sector and has a fairly high social value. Lingga Regency consists of 13 sub-districts and 84 villages. In North Lingga Sub-district, Pasir Lulun Preparatory Village is experiencing serious problems in the provision of electricity. Apart from PLN, the community relies on generators funded by the Village Fund. This study aims to assess the role of local government in electricity provision and the constraints faced. Using a descriptive qualitative method, this study relates the results to Soerjono Soekanto's Role of Government theory (Riyan Tika Syafitri, 2023). The findings show the government's role as regulator, dynamizer, and facilitator with geographical challenges, small population, and inadequate road infrastructure. The Lingga Regency Government has not been effective in equalizing village electricity development